Interconnections between Civilizations from Modern Times to the Present: A Historical-Critical Chronological Persective - Pasaribu, Timbul (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The concept of interconnection between civilizations, particularly from the modern era to the present, reflects the continuous transformation in the history of mankind. This paper examines the historical processes of civilizational interconnection that began in the Renaissance and continued through important phases such as the Industrial Revolution, colonialism, and the rise of globalization. It focuses on key historical moments that shaped the relationship between civilizations, examining the cultural, technological, economic and political exchanges that shaped relations between nations. Through a critical historical perspective, this paper discusses the challenges and opportunities presented by the interconnection of civilizations in the digital age, highlighting the complexities of cultural exchange amidst technological advancements. The paper also examines the dialectical relationship between the forces of cultural homogenization and the preservation of local identities, demonstrating the importance of building inclusive global relationships.The paper concludes by advocating a balanced, equitable, and cooperative approach to the interconnection of civilizations, which can enrich global culture and promote peace, while respecting the diversity of local cultures.